Regulatory role of N6-Methyladenosine on skeletal muscle development in Hu sheep - Jiang, Junfang; Guo, Liangyong; Huang, Xin; Zheng, Kaizhi; He, Sangang; Shan, Huili (Frontiers in Genetics, 2024)
N6-Methyladenosine (m6A) RNA modification plays an essential role in many biological processes. To investigate the regulatory role of m6A on the skeletal muscle development in Hu sheep, this study took newborn Hu sheep (b_B Group) and six-month-old Hu sheep (s_B Group) as the objects. MeRIP-seq and RNA-Seq analysis techniques were used to detect differentially methylated genes (DMGs) and differentially expressed genes (DEGs) in the longissimus dorsi muscle of Hu sheep at different months of age. Then, conjoint analysis was further employed to screen for key genes involved in skeletal muscle development that are modified by m6A and expressed by mRNA.According to the results of the MeRIP-seq analysis, there were 285 m6A differentially methylated peaks(DMPs) in total between b_B Group and s_B Group, with 192 significant up-regulated peaks and 93 significant down-regulated peaks. GO and KEGG analysis revealed that DMGs are mainly enriched in actin-binding, cellular transport, and metabolic pathways. According to the results of the RNA-seq analysis, there were 4349 DEGs in total between b_B Group and s_B Group, with 2010 up-regulated genes and 2339 down-regulated genes. DEGs are found to be mainly enriched in the regulation of actin cytoskeleton tissue, AMPK and FoxO signaling pathways, etc. The conjoint analysis demonstrated that 283 genes were both modified by m6A and expressed by mRNA. Among them, three genes relevant to muscle growth (RGMB, MAPK8IP3, and RSPO3) were selected as candidates for quantitative validation, and the results were in line with the sequencing results. The results mentioned above all suggest that m6A plays a certain role in the skeletal muscle development 2 in Hu sheep.